EXPLOITATION OF UNESCO WORLD HERITAGE OBJECTS IN TOURISM - N. Zamyatina; A. Zbarskaya (Вестник университета)
The article covers issues of the tourist region image compared to the exploita-tion of the World Heritage objects of UNESCO in tourism. Particular attention is paid to the need for strategic planning in tourism and the increasing responsibility in this regard for the exploitation of heritage monuments. At the same time, the need for full accessibility of tourist destinations and cultural heritage sites is emphasized. The authors emphasize that without a comprehensive approach to solving the problems of accessibility of UNESCO World Heritage sites, the tourist image of Moscow will be damaged, having an inevitable negative effect already in the long-term future.